Out of my mind - Draper, Sharon M (Sharon Mills) (New York Atheneum Books for Young Readers, 2010)
Considered by many to be mentally retarded, a brilliant, impatient fifth-grader with cerebral palsy discovers a technological device that will allow her to speak for the first time
Ages 10 up
2
Keywords: Cerebral palsy -- Fiction; Communication -- Fiction; Genius -- Fiction; Interpersonal relations -- Fiction; People with disabilities -- Fiction